WATER QUALITY RESEARCH NEAR OŠUPES MANOR - Erts, Ervīns; Laizāne, Ināra (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
In Galēnu center near Ošupes manor is pond which is next to the borehole. The problem was that the visual was observed that the pond and the borehole is discolored and had a smell so it was suspected that the water at both places is contaminated. Since the borehole was meant for drinking water, raised the question can it be used for drinking and or to these changes can blame pond which in near. In work process samples were collected from both the pond and from the borehole, which was delivered to the laboratory where they established a variety of chemical parameters from which it can be determined is the water is polluted. When carrying out checks it will be able to conclude whether the water near borehole is not harmful to human health, thereby protecting people from infection with different abdominal diseases.